2010
DOI: 10.1177/0272989x10371681
|View full text |Cite
|
Sign up to set email alerts
|

Is an Ounce of Prevention Worth a Pound of Cure? Comparing Demand for Public Prevention and Treatment Policies

Abstract: Preferences for public health policies vary markedly with policy attributes and with individual characteristics. Benefits measurements for welfare assessments of public health policies should be tailored to the type of health threat and the characteristics of the affected population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…(46) The reasons for this are unclear, but a likely set of possible explanations includes: (i) respondents may not believe the public programs will benefit them, (ii) respondents may not believe public programs will be effective, or (iii) respondents may focus their attention on the public nature of the program and be less attentive to the benefit to themselves. See also Bosworth et al (47) for a recent discussion of possible reasons why WTP for private risk reductions may be different from public risk reductions.…”
Section: Preliminary Analysis Variable Definitions and Expectationsmentioning
confidence: 99%
“…(46) The reasons for this are unclear, but a likely set of possible explanations includes: (i) respondents may not believe the public programs will benefit them, (ii) respondents may not believe public programs will be effective, or (iii) respondents may focus their attention on the public nature of the program and be less attentive to the benefit to themselves. See also Bosworth et al (47) for a recent discussion of possible reasons why WTP for private risk reductions may be different from public risk reductions.…”
Section: Preliminary Analysis Variable Definitions and Expectationsmentioning
confidence: 99%
“…Bulte et al (2005) find that the cause of an environmental problem influences individuals' WTP to fix it. Bosworth et al (2010) report that people are willing to pay more to reduce human mortality via prevention over treatment. Johnston and Duke (2007) test the hypothesis that policy processes are utility-neutral in a DCE on agricultural land preservation.…”
Section: Introductionmentioning
confidence: 99%
“…The question of 'cure' versus treatment has not been widely explored, although there is a large literature exploring treatment (often labeled 'cure' in these studies) versus prevention that may offer some insight [20][21][22][23]. These studies have revealed the relationship between individual and societal preferences for prevention versus treatment.…”
Section: How Much Value?mentioning
confidence: 99%